Day 4 Fri, March 25, 2016 2016
DOI: 10.4043/26668-ms
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Design Criteria for South China Sea With a Large-Scale Extreme Value Model

Abstract: Existing metocean design criteria for offshore facilities in the South China Sea have been estimated using different data and procedures, some of which are at least partly ad hoc. As a result, it is probable that existing criteria are inconsistent, in the sense that assets designed to the same design codes have different realised levels of integrity. To address this concern in this paper, we apply a large-scale extreme value model adapted to parallel computing environment, applied to the recent high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Past studies regarding wave height comparison between SEAFINE and field measurement showed varying results. The study by Ragupathi, et al [14] attempted to compare the peaks of SEAFINE and measured data, which revealed that the hindcast data were lower than the measured data collected near a platform in Offshore Serawak, Malaysia. In general, hindcast overestimates field measurements.…”
Section: Thementioning
confidence: 99%
“…Past studies regarding wave height comparison between SEAFINE and field measurement showed varying results. The study by Ragupathi, et al [14] attempted to compare the peaks of SEAFINE and measured data, which revealed that the hindcast data were lower than the measured data collected near a platform in Offshore Serawak, Malaysia. In general, hindcast overestimates field measurements.…”
Section: Thementioning
confidence: 99%
“…Recently, new deductive methods for data extrapolation were developed. These rely on non-stationary extreme value analysis, hereafter referred to as CEVA ("Covariate Extreme Value Analysis") and are described in ( [1], [18], [19], [20]). Briefly, CEVA performs a non-stationary directional-seasonal analysis of storm peak significant wave height using a penalized maximum likelihood approach.…”
Section: Introductionmentioning
confidence: 99%